(untitled) (Emancipação, 2025)
Social inequalities hinder access to healthcare services, especially for groups living in situations of social vulnerability. Persons with Disabilities who receive the Continuous Cash Benefit (BPC) are included in this context. This study aimed to analyze healthcare accessibility for these individuals, assessing whether comprehensive care is ensured by the Brazilian Unified Health System (SUS), their social conditions, and the financial impact of health-related expenses. Data were collected through interviews conducted in the municipality of Ponta Grossa, Paraná. Results were presented in tables and graphs, and the discussion was grounded in the literature and relevant Brazilian legislation. Findings indicate that, despite some progress in healthcare accessibility, this group continues to bear the burden of State inefficiency, ranging from bureaucratic barriers to shortcomings in the provision of medication and transportation.